Study Of Basal Physiological Parameters Of Standard X Students Of Dhule City - DR. AMITA. R. RANADE,; DR. GANESH. V. KULKARNI, (International Journal of Pharma and Bio Sciences, 2015)
Today few literatures are available regarding normative data of the basal physiological parameters for Indian population. So the present study is undertaken to study the basal physiological parameters of standard X students. We performed an observational study in 70 students of standard X. Various parameters were measured in these students namely: body mass index (BMI), % Body fat, basal blood pressure, heart rate, sympathetic activity test like cold pressure test & parasympathetic activity tests like lying to standing test and various pulmonary function test parameters. Values of all anthropometric, cardiovascular and respiratory parameters were within normal ranges for particular age groups when compared to standard western references. As basal physiological parameters are subjected to variation by age, sex, race, genetic factor etc, values obtained from our study can be considered as normal reference values for the Indian population.